Best Answer

-47 + 6z = 3z-2

-3z -3z

-47 + 3z = -2

+47 +47

3z = 45

/3 /3

z = 15

Q: - 47 plus 6z equals 3z - 2 what does z equal?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

63 plus 47 plus 42 plus 21 is equal to 173.

sixty is equal to 10 plus 50, and as 10 equals 50, and 50 equals 79, then it would be fair to assume that 60 equals 50 plus 79, which is 129.

Technically there are no variables in this equation, as 47 minus 25 is equal to x (22)

46 + 47 = 93

47 + 60 = 107

Related questions

63 plus 47 plus 42 plus 21 is equal to 173.

sixty is equal to 10 plus 50, and as 10 equals 50, and 50 equals 79, then it would be fair to assume that 60 equals 50 plus 79, which is 129.

Technically there are no variables in this equation, as 47 minus 25 is equal to x (22)

47+47=94

47 plus 61 is equal to 108.

47 + 60 = 107

46 + 47 = 93

46+1

74

124

V= 47. 81 + 47 - 13= 47.

29 x 47 = 1363